(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cascaded H-bridge multilevel inverters (CMLI) have become very popular, because they are able to generate voltage waveforms with negligible waveform distortion. The number of isolated input dc sources and switching devices are very high in conventional CMLI to get high levels. This paper presents an Asymmetrical Cascaded H-bridge Multilevel Inverter (ACMLI) which varies from the conventional cascaded multilevel inverter (CMLI) based on the number of sources and power devices used. The 27 level ACMLI is proposed for Uninterruptible Power Supply (UPS) which has only 3 input dc sources and 12 switching devices when compared to conventional twenty seven level CMLI. The 27 level ACMLI multilevel inverter for UPS application is simulated using MATLAB/simulink software and the results are obtained. The hardware prototype for the single phase 27 level ACMLI multilevel inverter is designed and implemented. The simulation results are validated with hardware results.